Program Literasi Keuangan Syariah bagi Pelajar dan Mahasiswa di Kota Bandung - Maksum, Hary; Ahmad, Yono Ali; Rahmawati, Laili (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
The Islamic financial literacy program for students in Bandung City aims to increase understanding and awareness of the principles of Islamic finance. In the context of globalization and rapid economic development, it is important for the younger generation to understand financial concepts that comply with sharia values. This study used a quantitative method with a survey approach to collect data from students in Bandung. The results show that the Islamic financial literacy program is effective in increasing knowledge and positive attitude towards Islamic finance. Thus, this program is expected to contribute to the development of Islamic economy in Indonesia.